Urban agglomeration and firm innovation: Evidence from Asia - Liming Chen; Rana Hasan; Yi Jiang (Asian Development Bank (ADB), 2020)
This paper presents evidence on the spatial distribution and effects of urban agglomeration on firm innovation. It uses a unique dataset that consistently defines city boundaries and identifies firms' innovation-related activities across 25 developing countries in Asia. We find firm innovation to be highly concentrated at the city level. We also find substantial gains from increases in city population in terms of firms' propensity to introduce process and product innovations and undertake research and development (R&D) activities. These gains remain even after addressing concerns regarding endogeneity through the use of historical population data as instruments. In addition, we present evidence that knowledge spillovers are an important channel through which agglomeration effects occur, specifically through the presence of top-tier universities in a given city and by raising the effectiveness of firms' R&D efforts. These findings confirm the existence and significance of urban economies of scale in augmenting the knowledge flows that generate innovation.
Keywords: O30; R11; O10; 330; agglomeration economies; innovation; knowledge spillovers